Affordance-based control in deceptive and non-deceptive penalties in soccer goalkeeping: Gender matters!. (January 2022) - Zheng, Ran; van der Kamp, John; Song, Xinyong; Savelsbergh, Geert
Abstract: Only few studies have addressed how soccer goalkeepers adapt to both the spatial and temporal constraints while trying to stop a penalty kick. Moreover, research on penalty kicks has only involved male goalkeepers, even though the resultant constraint (i.e., the relation between the maximum action capabilities defining the time required and ball flight time and direction defining the time available) may or may not differ for female goalkeepers. We therefore compared penalty goalkeeping between male and female goalkeepers of similar skill level. The results showed that the resultant constraint was more stringent for female than male goalkeepers. In accordance with the affordance-based control theory, female and male goalkeepers both adapted to the resultant constraint, but did scale their diving action differently. Female goalkeepers initiated the lateral dive within the action boundaries set by the resultant constraint, while male goalkeepers tended to dive late, beyond the action boundaries. Owing to the early dive, female goalkeepers saved more penalties than male in non-deceptive penalties. Nevertheless, female goalkeepers were also more susceptible to deception by the penalty taker than male goalkeepers. These findings extend our knowledge of the affordance-based control theory in sports and contribute to the understanding of gender differences in soccer penalty goalkeeping. Highlights: Female goalkeepers are confronted with more stringent resultant constraints compared to male goalkeepers. Female goalkeepers initiate the lateral dive earlier than male goalkeepers. The two genders adapt to the emerging dynamic constraint in the same manner, but exhibit different calibration. Female goalkeepers are more susceptible to deception of the kicker than male goalkeepers.